2023
DOI: 10.3389/fanim.2023.1125061
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a yeast β-glucan blend in a pet food application to determine its impact on stool quality, apparent nutrient digestibility, and intestinal health when fed to dogs

Abstract: Oral supplementation of β-glucans may be able to improve the health of companion animals. However, little is understood regarding the effects of yeast β-glucan on diet processing and intestinal function. Therefore, the objectives of this research were to determine the carry through of yeast β-glucan during extruded diet production and its impact on diet utilization by dogs. Three diets were formulated to contain increasing levels of a yeast β-glucan blend at 0, 0.012 and 0.023% inclusion. Processing inputs wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Bastos et al ( 5) also observed lower fecal ammonia levels after an abrupt dietary change in dogs supplemented with live yeast compared to control ones. However, these finding have not been consistent as other authors have reported higher fecal pH (82,90,95) or no change (24,74,81,86).…”
Section: -63 Daysmentioning
confidence: 55%
See 3 more Smart Citations
“…Bastos et al ( 5) also observed lower fecal ammonia levels after an abrupt dietary change in dogs supplemented with live yeast compared to control ones. However, these finding have not been consistent as other authors have reported higher fecal pH (82,90,95) or no change (24,74,81,86).…”
Section: -63 Daysmentioning
confidence: 55%
“…As a result of this, bacterial fermentation in the large intestine would be reduced as less fermentable substrate would be available. However, one should be cautious with this hypothesis as in vivo studies with yeast β-glucans have reported increases in apparent total tract digestibility (ATTD) in pre-ruminant calves (23) or no changes at all in dogs (24). Other possible mechanism of yeast to modulate nutrient digestibility is the production of enzymes, such as amylases, lipases, and proteases.…”
Section: Increased Digestibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it is important to filter that the beneficial bacteria responsible for metabolizing the oligosaccharides are strains of Lactobacilli and Bifidobacteria. The most known prebiotics and used by the petfood industry are lactulose, fructooligosaccharides (FOS), inulin, yeast cell wall, and mannanoligosaccharides (MOS) [6]; moreover, there has been a recent increase in the number of studies that have investigated the potential effects of beta-glucans [7]. However, in addition, there is a range of potential prebiotics that are being studied.…”
Section: Introductionmentioning
confidence: 99%